Analisis Framing Pemberitaan Detik.com, Program Makan Bergizi Gratis Prabowo-Gibran Di Makassar - Hatta, Harmin; Ramansyah; Mursalim, Muhammad Akram (JAMBURA JURNAL ILMU KOMUNIKASI, 2025)
This study aims to examine how online media Detik.com presents news about the implementation of the national program "Free Nutritious Meals" proposed by the elected President and Vice President, Prabowo Subianto and Gibran Rakabuming Raka, especially in Makassar City. The method used is descriptive qualitative analysis with the framing model approach from Pan and Kosicki, which includes aspects of syntax, script, theme, and rhetoric in the news structure. The research findings show that Detik.com tends to provide information in a neutral and procedural manner and focuses on administrative aspects and support from institutions, without exploring the views of the community who are direct beneficiaries. The news emphasizes more on the technical implementation of the program, the role of government officials, and cultural elements such as local menu proposals, but does not discuss the evaluation, challenges, or impact of the program on strategic issues such as stunting. This study highlights the importance of the role of the media in shaping the construction of social reality, while also showing the limitations in conveying the diversity of public narratives.